Exploring the formation and alteration of organics in ice: experimental insights for astrochemistry and space missions - Florence Hofmann; Nariste Asanova; Riccardo Giovanni Urso; Andreas Elsaesser (Earth, Planets and Space)
Abstract The formation and alteration of organic molecules within the Solar System and beyond is closely related to the life cycle of ice in space. Cold molecular clouds in the interstellar medium (ISM) are regions, where volatile molecules condense onto submicron-sized dust grains. Throughout their lifetime, these interstellar ice particles are exposed to energetic photons, charged particles and thermal processing, which catalyze the formation of increasingly complex organic compounds and induce the desorption of volatile species. The accretion of these compounds into comets and asteroids would allow their delivery on planetary surfaces, making them potential precursors of the building blocks of life. Alongside comets and asteroids, complex organics are also present on the icy moons of giant planets which are targets in both NASA’s and ESA’s space exploration programs. In this paper, we present a new experimental setup, built to study the formation and alteration of complex organic molecules of astrobiological-relevance in cryogenic environments. Possible samples include inorganic and organic molecules, in contact with various ice mixtures (e.g., H2O, NH3, CO, CO2, CH3OH) which can be exposed to UV photons, electron bombardment and undergo thermal processing. The setup allows continuous monitoring by Fourier transform-infrared (FT-IR) transmission spectroscopy during the ice formation, irradiation-, and warm-up. We present FT-IR measurements of pure H2O, pure NH3 and pure CH3OH ice samples deposited at 15 K and we show the main spectral changes induced by heating and electron bombardment. Furthermore, we show the formation of new molecular species within NH3:CH3OH and NH3:CH3OH:H2O ice mixture under electron bombardment, and outline an experimental design used to investigate the stability of organic molecules under simulated conditions on icy moons. With our setup we envision to provide spectral information on astrobiologically-relevant molecules, such as organic species fundamental for living organisms and potential biosignatures, in contact with ices of relevance for astrophysics and planetary science. Graphical Abstract